Q-error Bounds of Random Uniform Sampling for Cardinality Estimation - Li, Beibin; Lu, Yao; Wang, Chi; Kandula, Srikanth (Microsoft, 2021)
Random uniform sampling has been studied in various statistical tasks but few of them have covered the Q-error metric for cardinality estimation (CE). In this paper, we analyze the confidence intervals of random uniform sampling with and without replacement for single-table CE. Results indicate that the upper Q-error bound depends on the sample size and true cardinality. Our bound gives a rule-of-thumb for how large a sample should be kept for single-table CE.